Immune function against bacteria of chitin deacetylase 1 (EcCDA1) from Exopalaemon carinicauda. Issue 75 (April 2018) - Sun, Yuying; Zhang, Jiquan; Xiang, Jianhai
Abstract: Chitin deacetylase (CDA, EC 3.5.1.41), belonging to a family of extracellular chitin-modifying enzymes, can catalyze the deacetylation of chitin. In this study, the full-length cDNA sequence encoding chitin deacetylase 1 ( EcCDA1 ) was obtained from Exopalaemon carinicauda . The complete nucleotide sequence of EcCDA1 contained a 1611 bp open reading frame (ORF) encoding EcCDA1 precursor of 536 amino acids. The domain architecture of the deduced EcCDA1 protein contained a signal peptide, a chitin-binding peritrophin-A domain (ChtBD2), a low-density lipoprotein receptor class A domain (LDLa) and a Polysacc_deac_1 domain. EcCDA1 mRNA was predominantly expressed in the gills. The expression of EcCDA1 in the prawns challenged with Vibrio parahaemolyticus and Aeromonas hydrophila changed in a time-dependent manner. The expression of EcCDA1 in the prawns challenged with V. parahaemolyticus was up-regulated at 12 h ( p  < 0.05), and significantly up-regulated at 24 h and 48 h ( p  < 0.01), and then returned to the control levels at 96 h post-challenge ( p  > 0.05). At the same time, the expression in Aeromonas -challenged group was significantly up-regulated at 12, 24 and 48 h ( p  < 0.01) and returned to the control levels at 120 h post-challenge ( p  > 0.05). Then, EcCDA1 was recombinantly expressed in Pichia pastoris and the purified recombinant EcCDA1 could not inhibit the growth of V. parahaemolyticus or A. hydrophila, which indicated that the CDA1 may play its biological activity in immune defense by deacetylation from chitin. Highlights: EcCDA1 was predominantly expressed in gills of E. carinicauda. EcCDA1 was upregulated after challenge with V. parahaemolyticus or A. hydrophila. We first demonstrate the immune function of EcCDA1 against bacteria.